Hearing impairment and associated socio-demographic characteristics in patients with tinnitus - Khan, Danish A.; Varshney, Pramod K.; Zubair, M. Yasir; Anas, M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Tinnitus is a common ear problem and causes various somatic and psychological effects that has a bearing on the quality of life. Considerably high prevalence, distressing nature of the problem and the fact that it is associated with hearing impairment warrants an early recognition and appropriate timely intervention. Methods: A total of 120 patients (60 with tinnitus and 60 without tinnitus) were included in the study. Data of putative socio-demographic factors and clinical examination findings were collected on a semi-structured questionnaire. Results: The mean age of patients with tinnitus was 38.12±13.39 while that of patients without tinnitus was 40.85±15.26 (p=0.299). Around two-thirds (63.33%, 95% CI, 51.3–75.7%) of patients with tinnitus were males and the other one-third (36.67%, 95% CI, 24.3–48.7%) were females. Two-thirds (66.7%, 95% CI, 54.6–76.7%) of patients with tinnitus belonged to urban locality and the remaining one-third (33.3%, 95% CI, 23.3–45.4%) were from rural areas. On pure tone audiometry (PTA), hearing impairment was detected in 32 (53.3%, 95% CI, 42.0–68.3%) patients with tinnitus as compared to 13 (21.7%, 95% CI, 9.3–35.4%) patients without tinnitus. Conclusions: Tinnitus was associated with hearing loss in considerable proportion irrespective of patients’ own awareness of hearing loss. Therefore, patients should be educated regarding importance of seeking early healthcare. Although the benefits of available treatments are small, and the perception of tinnitus does not wane completely, it improves quality of life and reduces distress resulting from tinnitus.